2012
DOI: 10.1103/physrevlett.108.264504
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Fracturing in Granular Media

Abstract: We study the displacement of immiscible fluids in deformable, noncohesive granular media. Experimentally, we inject air into a thin bed of water-saturated glass beads and observe the invasion morphology. The control parameters are the injection rate, the bead size, and the confining stress. We identify three invasion regimes: capillary fingering, viscous fingering, and "capillary fracturing," where capillary forces overcome frictional resistance and induce the opening of conduits. We derive two dimensionless n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
135
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(146 citation statements)
references
References 30 publications
10
135
0
Order By: Relevance
“…Finally, a new regime was reported in the 2D experiment, with a transition between the growth of an air finger and the fracture of the above granular layer at a given height in the cell. Such patterns as fingering and fracturing have been reported in the literature in deformable, saturated porous media, when varying the grain volume fraction [40,55,56]. These patterns, however, were mainly described for horizontal Hele-Shaw cell, in which buoyancy does not govern the system dynamics.…”
Section: Discussionmentioning
confidence: 87%
“…Finally, a new regime was reported in the 2D experiment, with a transition between the growth of an air finger and the fracture of the above granular layer at a given height in the cell. Such patterns as fingering and fracturing have been reported in the literature in deformable, saturated porous media, when varying the grain volume fraction [40,55,56]. These patterns, however, were mainly described for horizontal Hele-Shaw cell, in which buoyancy does not govern the system dynamics.…”
Section: Discussionmentioning
confidence: 87%
“…Rust et al developed a closed-system degassing model using volcanic eruption data [35]. Holtzman et al also studied air induced fracturing where they identified different invasion regimes [36]. Furthermore, a recent study was conducted by Eriksen et al where the air injection causes bubbles in a fluid-grain mixture [37].…”
Section: Introductionmentioning
confidence: 99%
“…For example, one observes flow regimes such as two-phase flow in rigid porous media [40][41][42][43][44], capillary fracturing, stick-slip bubbles, and labyrinth patterns [31][32][33][34][35][36][37][38][39]. In the opposite case, during liquid injection into dry granular media [45], for a given imposed flux, the flow behavior goes from stable invasion toward saturated granular fingers for increasing flow rate and viscosity of the invading fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Further, during air injection into liquid saturated granular media and suspensions, the characteristics of emerging patterns and behavior of the media depend on injection rate and the competition between mobilized friction and surface forces [31][32][33][34][35][36][37][38][39][40][41][42][43][44]. For example, one observes flow regimes such as two-phase flow in rigid porous media [40][41][42][43][44], capillary fracturing, stick-slip bubbles, and labyrinth patterns [31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%